Pengaruh Employee Stock Ownership Program (ESOP), Leverage, Ukuran Perusahaan, dan Umur Perusahaan Terhadap Kinerja Keuangan - Yuniawati, Silvia; Prihatni, Rida; Sumiati, Ati (LPPM Universitas Negeri Jakarta, 2024)
Optimal financial performance is crucial for the sustainability and growth of a company. The purpose of this study is to evaluate the impact of the Employee Stock Ownership Plan (ESOP), leverage, company size, and company age on financial performance. The population in this study includes 44 transportation entities registered on the Indonesia Stock Exchange for the period 2020-2022. This research utilizes additional data, specifically audited annual financial reports from 2020-2022, which are accessible through the IDX website. The purposive sampling technique was applied in the sampling process of this study, resulting in 114 data observations. Data were processed using IBM SPSS version 26 software, which was used for time series data testing and multiple linear regression analysis. This study found that ESOP has a positive impact on financial performance, company age has a negative effect on financial performance, while leverage and company size do not show a significant influence on financial performance.